Investigation on Effect of Cutting Fluid Pressure Toward Machinability Using Stainless Steel 304 With Coated Cemented - Zainal Ariffin, Selamat; Razali, M.; A. R., Yusoff; M. M., Rahman (AENSI Publishing, 2014)
This paper presents the effects of cutting fluid pressure on various orifice nozzle sizes on the cutting performances. Cutting fluid is generally being used in metal cutting to optimize the machining operation process. The objectives of this study are to investigate the effects of various cutting fluid pressures on the stainless steel AISI 304 and the effect of the cutting performance on machining parameters such as tool wear, tool life and surface roughness. Stainless steel AISI 304 and coated cemented carbide, Al2 O3 insert were used as work piece material and cutting tool respectively. The experiments were carried out on CNC Lathe machine by using various orifice nozzle sizes with synthetic soluble oils as a coolant. The results showed that Al2 O3 insert gives good overall performance in terms of tool life and better surface roughness when the smallest orifice size is used.